Votive stone carvings from Tibiscum. Local production and import - BALACI CRÎNGUŞ, Mariana; BALACI, Cătălin (Studia Universitatis Babeș-Bolyai Historia, 2016)
Tibiscum is an important military and civilian settlement from south-western part of Dacia Superior. In the fort several units were garrisoned, mainly from oriental provinces of the Empire and beside the fortification the civil settlement quickly flourished and in the beginning of the IIIrd century AD the settlement here become a municipium or at least some part of it. The votive stone carvings discovered in the fort, the vicus or the municipium represent, in general, Greco-Roman divinities regardless of the fact that the main troops forming the garrison here were of oriental origin. Were discovered representations of Jupiter, Diana, Mercury, Silvanus, Liber Pater, Venus, Hercules etc.; along them several representation of Danubian Riders and two Epona representations. Some votive carvings were made in stone workshops from Ulpia Traiana Sarmizegetusa, others were made somewhere in the South of the Danube line and some others are made locally. The ones produced locally are easy traceable because they are of small size and very schematized. Rezumat. Sculpturi votive de la Tibiscum. Producţie locală și importuri. Tibiscum este o importantă așezare militară și civilă din Dacia Superior. Castrul era garnizoana mai multor unităţi, în special din provinciile orientale ale Imperiului și pe lângă fortificaţie a înflorit o așezare civilă care, în secolul al III-lea p. Chr., a devenit municipium, sau cel puţin o parte a acesteia. Reliefurile în piatră descoperite în castru, vicus sau municipium, înfăţișează în general divinităţi greco-romane, în ciuda faptului că unităţile principale care formau garnizoana erau de origine orientală. Au fost descoperite statui și reliefuri care înfăţișează pe Iupiter, Diana, Mercurius, Silvanus, Liber Pater, Venus, Hercules etc., și, pe lângă acestea, câteva reprezentări ale Cavalerilor Danubieni și două reliefuri ale zeiţei Epona. Unele au fost realizate în atelierul de la Ulpia Traiana Sarmizegetusa, altele provin din ateliere de la sud de Dunăre și unele au fost produse în atelierul local. Produsele locale sunt ușor de recunoscut pentru că sunt de dimensiuni mici și foarte schematizate. Cuvinte cheie : Reliefuri votive, ateliere de pietrărie, producţie locală, divinităţi greco-romane